Electrochemical recovery of alkali and hydrogen gas from desalination brine - Lim, Guan Chun (Nanyang Technological University, 2024)
Desalination brine, the waste product from the seawater desalination process, poses a major threat to the marine ecosystem without proper treatment and disposal. As an alternative to direct disposal of seawater desalination brine, electrolysis is a promising strategy for waste minimization, carbon capture, and hydrogen production by breaking down the waste brine from desalination after removing Ca and Mg compounds as the pretreatment process. Integrating carbon capture, utilization, and storage (CCUS) with brine utilization, hydrogen gas, and alkali produced from the electrolysis process offers a significant synergistic system to simultaneously address climate change and water scarcity challenges. To analyze the possibility of recovering the desalination brine as a decarbonization strategy, a membrane flow cell has been proposed and developed to reuse the brine. In this report, Ni foam is used as the cathode's electrocatalyst and was analyzed using reverse linear scan voltammetry and chronoamperometry to validate its catalytic activity toward hydrogen evolution reaction (HER) and oxygen reduction reaction (ORR). For all the electrolytes tested i.e., 1M NaOH, 1M carbonate solution, 1M bicarbonate solution and R2 (desalination brine after addition of NaOH), around 90% of Faradaic efficiency (FE) is achieved when potential applied to the electrolytic flow cell reaches 1.4 V. At low potential of 1 V and 1.2 V, ORR reaction is competing with HER reaction, which is projected in 1 M Na2CO3 solution under oxygen-rich condition. The Tafel analysis and FE calculation results validated that ORR reaction is favourable for R2 solution under any applied potential and other buffer solutions under low potential conditions.